Preparation and Characterization of Superconducting Thin Films - Azman, Nur Helmi @ Nur Jannah (2004)
The future application of high temperature superconductor (HTSs) in cryoelectronic devices, which are capable of operating at temperatures typically between 20 K and 77 K will strongly depend on the development of a reproducible deposition technology of high-quality single and multilayer HTS thin films. In this work, Bi1.6Pb0.4Sr2Ca2Cu3Oy and YBa2Cu3Ox thin films have been fabricated by pulsed laser deposition onto MgO single crystal substrate with the (100) orientation. Nine series of Bi(Pb)SrCaCuO thin films with different deposition times (thickness) were annealed at different annealing temperature (850ºC, 860ºC, 870ºC, and 880ºC) under oxygen flow. One series of YBCO thin films were annealed at different duration time under oxygen flow. By varying the deposition parameters, films showing different kinds of particulates and surface morphology were fabricated. The most prominent types of particulates for BSCCO films on MgO substrate are droplets with various shapes and sizes. The droplets are randomly oriented and submicron rod-like features are also observed. Needles, platelets, irregularly-shaped Cu-rich outgrowths, tabular outgrowths and big target fragments are also detected. Droplets that have been observed might be due to the crystallization effect on the hot substrate. The target morphology, which develops under laser-irradiation, has also been investigated. Morphological changes for the target take the form of periodic structures such as ripples, ridges, and cones. Both x-ray diffraction and resistive measurements indicate that the BSCCO superconducting phase does not form for the as-deposited films since the peak related to the formation of crystalline phases were not observed. Most films showed slight decrease in resistance at 110-120 K after heat-treatment. Zero resistances were registered in the range of 60-68 K. This range is strongly dependent on the annealed temperature. The AFM, SEM, EDX, XRD patterns and Tc measurements indicate that the films were mainly dominated by the 2212 phase, with rather poor evidence for the 2223 phase. The attempt to obtain high Tc superconducting film from a superconducting target of 2223 phase gave poor results probably due to the non optimized heating conditions. Results obtained from characterization of the films, showed that annealing time and temperature, deposition times (thickness) influence the growth of superconducting phases. Since the exposed surface area-to-volume ratio is higher for a film than a bulk sample, this would explain why lead losses are apparently more dramatic for films than for a bulk material. The AFM three dimension image shows the island-growth mode of thin films. This mode may be correlated to the existence of clusters in the plasma. Annealing treatments have shown to be an effective method to change the oxygen in the BSCCO system and vary its superconducting properties. Although the superconducting properties of the films described are not as good as those prepared using an excimer laser, they can be improved further by optimizing various deposition parameters.